2013
DOI: 10.1159/000354251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vital Dyes on Retinal Pigmented Epithelial Cell Viability and Apoptosis: Implications for Chromovitrectomy

Abstract: Purpose: To investigate the in vitro effect of vital dyes on toxicity and apoptosis in a human retinal pigment epithelial cell line. Methods: ARPE-19 cells were exposed to brilliant blue (BBG), Evans Blue (EB), bromophenol blue (BroB), indocyanine green (ICG), infracyanine green (IfCG), light green (LG), fast green (FG), indigo carmine (IC) and Congo red (CR). Balanced salt solution was used as the control. Five different concentrations and 2 exposure times were tested. Cell viability was determined by the MTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…661W cells were serum‐starved over 24 h and treated with 20 μ m Norgestrel. Cell viability was then compared to non‐serum‐starved control (100% viability) using the MTS assay, an assay frequently used in ocular studies as a measure of cellular proliferation and viability (Penha et al ., ; Sobolewska et al ., ). Norgestrel significantly increased cellular viability after serum deprivation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…661W cells were serum‐starved over 24 h and treated with 20 μ m Norgestrel. Cell viability was then compared to non‐serum‐starved control (100% viability) using the MTS assay, an assay frequently used in ocular studies as a measure of cellular proliferation and viability (Penha et al ., ; Sobolewska et al ., ). Norgestrel significantly increased cellular viability after serum deprivation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The results are relatively heterogenous. While Haritoglou et al [4] did not observe any undesired effects at dye concentrations of 0.2 and 2 mg/mL and exposure times of 10 min, the results of Penha et al [5] indicated reduced cell viability at all concentrations tested (0.005 to 1.0 mg/mL) and at a dye contact time down to 3 min. Cell viability in the experiments by Balaiya et al [6] revealed toxicity at longer exposure times (30 min) of 0.5 mg/mL bromphenol blue concentrations, and apoptosis was observed already after 5 min of dye exposure.…”
Section: Retinal Pigment Epithelium Cell Culturesmentioning
confidence: 85%
“…The following observations were especially worrying: 1. In RPE cell culture experiments, undesired effects have been observed at concentrations below that presently available (1.3 mg/mL) and at relatively short exposure times (3-5 min) [5,6]. 2.…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, the ability of Norgestrel to rescue 661W cells from apoptoticinduced, serum starved cell death was investigated using the MTS assay for cellular proliferation and viability. This is a well-practised method in ocular studies (Okumichi et al 2008;Guerin et al 2011;Penha et al 2013;Sobolewska et al 2013). Norgestrel significantly inhibited apoptotic cell death by approximately 10% (*p < 0.05) (Fig.…”
Section: Discussionmentioning
confidence: 96%